Georgia : Fourth Review Under the Extended Fund Facility Arrangement and Request for Modifications of Quantitative Performance Criteria-Press Release; Staff Report; and a Statement by the Executive Director for Georgia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
Recent economic developments. Economic performance remained robust in 2018: growth reached 4.7 percent, supported by external demand; inflation stayed below the three percent target, the fiscal deficit remained in line with program commitments, and the current account improved. Tighter lending standards helped decelerate credit growth towards more sustainable levels. The banking sector remains well capitalized, liquid, and profitable. Dollarization remains elevated. In early 2019, growth conditions were favorable, with average inflation slightly above the target reflecting increased excises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet